Analysis of lipase activity in duodenal juice. Comparison of an automated spectrophotometric assay to a fluorometric microplate assay, and factors affecting sample stability. (2nd November 2018) - Tjora, Erling; Erchinger, Friedemann; Engjom, Trond; Aksnes, Lage; Dimcevski, Georg; Gudbrandsen, Oddrun Anita
Abstract: Background: Direct pancreas function testing (DPFT) has been regarded as gold standard for assessment of exocrine pancreas function. One of the outcomes from DPFT is pancreatic lipase activity in duodenal juice, but no standard assay for measuring pancreas lipase activity in duodenal juice exists. Aims: To optimize and evaluate an autoanalyzer assay for measuring lipase activity in duodenal juice. Methods: We used samples of duodenal juice from our biobank, collected through a short endoscopic secretin test in patients with suspected exocrine pancreas insufficiency. Samples were analyzed on a Cobas autoanalyzer (Roche Diagnostics), using a colorimetric, kinetic enzyme activity assay. We compared stability of samples diluted in saline to samples diluted in 3-( N -morpholino) propane sulfonic acid (MOPS) buffer added bovine serum albumin (BSA). Results from the Cobas assay were compared to Confluolip method, a fluorometric, kinetic enzyme assay, modified to fit into a microplate setting. Results: We tested the stability of 54 samples from 21 patients. Diluting samples with MOPS buffer added BSA gave stable results, and was superior to diluting samples in saline. We compared the two assays in 50 samples from 20 patients and found a good correlation between the two assays ( r  = 0.91, p  < .001). There was a significant proportional bias between the two assays, but no significant systematic bias. Conclusion: Pancreatic lipase activity in duodenal juice samples diluted in MOPS buffer added BSA is stable for one hour at room temperature. Quantification of lipase activity in duodenal juice using a standard automated activity assay has comparable accuracy to a manual fluorometric method.